Ascending to excellence: elevating Kone´s potential in vertical mobility - Wägner, Daniel (2023)
Amidst the challenges confronting the manufacturing sector, including supply chain disruptions, rising costs, and interest rate hikes, this equity research paper zooms in on the unique elevator and escalator industry. With a specific focus on Kone Corporation, the analysis delves into its strategic positioning and valuation, aiming to furnish investors with comprehensive insights. Serving as a crucial resource, this paper caters to potential investors seeking profound understanding not only of Kone Corporation but also the broader Elevator and Escalator Industry. In a climate where well-informed investment decisions are paramount, this study is meticulously crafted to illuminate pivotal considerations. Through a blend of qualitative and quantitative analyses, it empowers investors to navigate the intricate landscape of equity investments with confidence, facilitating informed decision-making